BENTUK PERAHU NELAYAN TRADISIONAL CILACAP PRAFIBERISASI - Rochyat, Indra Gunara; Widyastutieningrum, Sri Rochana; Sunarto, Bambang; Sunarmi, Sunarmi (Universitas Negeri Malang, 2022)
Traditional wooden fishing boats in Cilacap have a characteristic shape as a marker of their territory. The preservation of the shape of the boat until the era of fiberglass of materials became an ontological problem that was formulated. A phenomenological approach to the design of wooden boats is used in reviewing the content of values in the form at a certain time. The design element review method dissects various needs related to aspects of practicality, aesthetics, and symbols and combinations of the three, according to the geographical situation, and living conditions. The formation of the wooden fishing boat elements supported by the guiding elements is always related in a unit that influences each other. The intrinsic value in the shape of the wooden boat that was instilled by the previous fishermen was maintained by the next generation.Perahu kayu nelayan tradisional di Cilacap memiliki ciri bentuk sebagai penanda wilayahnya. Bertahannya bentuk perahu sampai pada era bahan fiberglass menjadi sebuah persoalan ontologis yang dirumuskan. Pendekatan fenomenologis pada desain perahu kayu digunakan dalam meninjau kandungan nilai-nilai pada bentuk di suatu kurun waktu tertentu. Metode tinjauan elemen desain membedah berbagai kebutuhan yang berkaitan dengan aspek kepraktisan, estetika dan simbol-simbol serta kombinasi-kombinasi dari ketiganya, sesuai dengan situasi geografis, dan kondisi-kondisi kehidupannya. Terbentuknya elemen perahu kayu nelayan ditopang oleh unsur-unsur pemandu itu senantiasa berkaitan dalam sebuah unit yang saling mempengaruhi satu sama lain. Nilai instrinsik pada bentuk perahu kayu yang ditanamkan oleh nelayan terdahulu terus dipertahankan oleh generasi sesudahnya.